P153 Quantum blue anti-adalimumab: development and evaluation of a point of care rapid test for measuring anti-adalimumab antibodies in human serum. (25th January 2019) - Ricken, B; Schneider, M; Bantleon, F; Velayutham, S; Trapani, D; Afonso, J; Magro, F; Abel, A
Abstract: Background: Patients suffering from inflammatory bowel disease (IBD) treated with adalimumab might not respond to the biologic at all, or might suffer from a secondary loss of response (SLR). A SLR is often caused by an immune response during which neutralising anti-adalimumab antibodies (ADADs) may develop. These ADADs are by nature of different isotypes and vary in their affinity and specificity towards their biologic target. The development of ADADs causes a significant decrease of the biologic's trough level. A rapid test for the detection of ADADs is therefore crucial and allows the adaptation of the treatment regime. In order to detect all varieties of ADADs it is inevitable to have an assay which is not limited to one specific antibody isotype. Methods: A drug-sensitive sandwich lateral flow assay was developed using adalimumab coated gold nanoparticles and an adalimumab capture on the membrane, allowing the detection of drug neutralising anti-adalimumab antibodies in human serum samples. The calibration is performed with calibrators based on human serum, spiked with monoclonal human ADAD. Real patient samples were used to compare the Quantum Blue ® Anti-Adalimumab rapid test with a commercially available ELISA test. Results: The Quantum Blue ® Anti-Adalimumab rapid test allows the analysis of diluted human serum samples within 15 min. A single 1:10 dilution step of the serum sample is required before sample loading onto the test cassette (volume 80 μl). The readout is performed with a Quantum Blue ® Reader resulting in a preliminary measuring range of 0.5 to 12.5 μg/ml. Due to missing international standard material for ADAD and the polyclonal immune response in patients, the Quantum Blue ® Anti-Adalimumab was classified as semi-quantitative. By testing patient samples a good diagnostic agreement between the Quantum Blue ® Anti-Adalimumab and the commercial ELISA was achieved. Conclusions: The Quantum Blue ® Anti-Adalimumab rapid test allows a fast detection of anti-adalimumab antibodies in human serum samples. The assay can be carried out with a minimum of external equipment and may therefore support a fast adaption of the treatment regime, providing a valuable tool for pro-active therapeutic drug monitoring.